ANALISIS MAKNA PROPERTI TARIBALINGGANG BAGA’ PADA SUKU DAYAK BAKATI’ RARAKABUPATEN BENGKAYANG - Tecla, Susana; Ismunandar, Ismunandar; Fretisari, Imma (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2018)
AbstractThe background of this research in which there are unique features of property form and clothing used by Balinggang Baga’ dance. Specifically, the problem of this research is how the form property and the meaning of Balinggang Baga’ property Bengkayang Regency.The method used in this research is descriptive method with a form of qualitative research. The approach used is semiotics is the science of signs. Sources of data in this study Mr Bujang, Mr. Nadu and Mrs. Niti. Mechanical testing the validity of data in the form of an extension of the observation and triangulation. The results of this study is to analyze the meaning of dance Balinggang Baga’ property ', is meetings with speakers who know the history of dance Balinggang Baga'. Analyzing the form and meaning dance property Balinggang Baga'through interviews with informants.Forms of property that resembles a woman trusted by the community to provide fertility for married couples and safety for a mother who will give birth. As for the meaning in the form of clothing used by mayang is interpreted as the identity of a woman Clothing consists of kebaya, jamu, samagk muag, roma, riti papatn and penggillar, keliang and galagk. Keywords: The meaning, Dance property, Balinggang Baga’